Andy Warhol and the Aesthetics of Everyday Life - Leddy, Thomas (Scenari, 2023)
Andy Warhol presents us with interesting insights into the aesthetics of life and of everyday life in his book The Philosophy of Andy Warhol. Like Plato, he presents a utopia, an ideal society, which has its own profoundly aesthetic character; he valorizes beauty; and he asks what beauty is. But, unlike Plato, and like John Dewey, he is a pragmatist and fiercely anti-dualist: for him beauty is a matter of context, and his utopia is democratic. I also contrast him with Arthur Danto, the later philosopher being fundamentally like Plato in that he posits two realms. Whereas Plato holds up the realm of the Forms, which are real, as superior to the realm of appearances, which are not, Danto distinguishes the realm of everyday life, of “mere things,” and the artworld. Mere objects advance ontologically as they are transfigured into the artworld. Rather than transfiguring objects into the realm of art, Warhol deconstructs the distinction between art and life. In this respect one can see him as, like Diogenes of Sinope, a philosopher qua performance artist. He does things, and his actions make philosophical points.